A short, animated storytelling video about sodium intake as a major cardiovascular risk factor and recommendations for a healthy diet: an online, randomized, controlled trial - Supady, Alexander; Nguyen, Kinh; Abd El Aziz, Mirna Safia; Überreiter, C.; Bärnighausen, Till; Adams, Martin (Trials, 2023)
Increased uptake of sodium is a major cause for cardiovascular disease and mortality. Reduction of daily salt intake below a reference level of 2 g per day (the equivalent to 5 g salt/day) is known to effectively reduce cardiovascular mortality. The widespread use of social media, with a constant increase in video consumption, is opening new avenues for the dissemination of innovative and scalable approaches to health-related information and recommendations for a healthy diet, such as via video interventions with short animated stories (SAS).